2022
DOI: 10.1186/s10020-022-00533-1
|View full text |Cite
|
Sign up to set email alerts
|

Spermidine protects against acute kidney injury by modulating macrophage NLRP3 inflammasome activation and mitochondrial respiration in an eIF5A hypusination-related pathway

Abstract: Background Acute kidney injury (AKI) is still a critical problem in clinical practice, with a heavy burden for national health system around the world. It is notable that sepsis is the predominant cause of AKI for patients in the intensive care unit and the mortality remains considerably high. The treatment for AKI relies on supportive therapies and almost no specific treatment is currently available. Spermidine is a naturally occurring polyamine with pleiotropic effects. However, the renoprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 60 publications
(79 reference statements)
0
11
0
Order By: Relevance
“…Hederasaponin C, a natural product, effectively inhibits lipopolysaccharide (LPS)-induced acute kidney injury in mice by specifically targeting Toll-like receptor 4 (TLR4) and modulating the phosphatidylinositol 4,5-bisphosphate (PIP2)/NF-κB/NLRP3 signaling pathway [ 254 ]. Spermidine, another natural molecule, protects against kidney injury by downregulating NLRP3 inflammasome activation and IL-1β production in renal macrophages [ 255 ]. Fisetin, a flavonoid, ameliorates renal fibrosis in the UUO mice model by inhibiting Smad3 phosphorylation [ 256 ].…”
Section: Therapeutic Potential Targeting Macrophages and Its Signalin...mentioning
confidence: 99%
“…Hederasaponin C, a natural product, effectively inhibits lipopolysaccharide (LPS)-induced acute kidney injury in mice by specifically targeting Toll-like receptor 4 (TLR4) and modulating the phosphatidylinositol 4,5-bisphosphate (PIP2)/NF-κB/NLRP3 signaling pathway [ 254 ]. Spermidine, another natural molecule, protects against kidney injury by downregulating NLRP3 inflammasome activation and IL-1β production in renal macrophages [ 255 ]. Fisetin, a flavonoid, ameliorates renal fibrosis in the UUO mice model by inhibiting Smad3 phosphorylation [ 256 ].…”
Section: Therapeutic Potential Targeting Macrophages and Its Signalin...mentioning
confidence: 99%
“…Maadawy, Walaa H et al [96] found that 6-Paradol alleviates diclofenac induced AKI by regulating autophagy enhancement mediated by AMP-activated protein kinases/AKT kinase/mammalian target of rapamycin (AMPK/AKT/mTOR) and the NLRP3 inflammasome pathway. Li et al [97] found that spermidine improved AKI by inhibiting the activation of the NLRP3 mediatedinflammasome in macrophages. Collectively, these studies provide evidence that inhibition of inflammasome activation could improve AKI.…”
Section: Inflammasomementioning
confidence: 99%
“…Spermidine, synthesized by putrescine and S-adenosylmethionine, exhibits multiple biological functions, including cell differentiation, proliferation, angiogenesis, gene expression, anti-aging, anti-inflammatory, and anticancer activities (Madeo et al, 2018;Pegg, 2014). Specifically, spermidine can prevent sepsis-induced acute kidney injury by downregulating the Nod-like receptor family pyrin domain containing 3 inflammasomes and interleukin-1β in macrophages (Li et al, 2022). Furthermore, spermidine can improve the function of human cells and delay aging (Madeo et al, 2018;Wang et al, 2020;Xu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%